2020
DOI: 10.3389/fneur.2020.569333
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Olfactory Function—Early Indicator for Covid-19, Other Viral Infections and Neurodegenerative Disorders

Abstract: The loss of the senses of smell (anosmia) and taste (ageusia) are rather common disorders, affecting up to 20% of the adult population. Yet, this condition has not received the attention it deserves, most probably because per se such a disorder is not life threatening. However, loss of olfactory function significantly reduces the quality of life of the affected patients, leading to dislike in food and insufficient, exaggerated or unbalanced food intake, unintentional exposure to toxins such as household gas, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 187 publications
(210 reference statements)
0
53
0
1
Order By: Relevance
“…Loss of smell and/or taste are common clinical manifestations that have long been associated with a spectrum of medical conditions, including neurodegenerative diseases such as Alzheimer's, in which olfaction is affected. 1 The evidence associating these clinical symptoms to COVID-19 has led to their inclusion on the list of COVID-19 symptoms by the Unites States Centers for Disease Control in April 2020 and brought these symptoms to the spotlight. The olfactory disturbances (anosmia) typically observed in upper respiratory infections are associated with inflammation and irritation of nasal mucosa or nasal blockage (rhinitis).…”
Section: Commentary and Analysismentioning
confidence: 99%
“…Loss of smell and/or taste are common clinical manifestations that have long been associated with a spectrum of medical conditions, including neurodegenerative diseases such as Alzheimer's, in which olfaction is affected. 1 The evidence associating these clinical symptoms to COVID-19 has led to their inclusion on the list of COVID-19 symptoms by the Unites States Centers for Disease Control in April 2020 and brought these symptoms to the spotlight. The olfactory disturbances (anosmia) typically observed in upper respiratory infections are associated with inflammation and irritation of nasal mucosa or nasal blockage (rhinitis).…”
Section: Commentary and Analysismentioning
confidence: 99%
“…Following an accumulation of publications in 2020, it has become widely accepted that complete (anosmia) or partial (hyposmia or microsmia) loss of olfaction as well as the loss of taste (ageusia) are common symptoms induced by SARS-CoV-2 ( [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] ). Due to its early onset during the disease course, it was proposed that olfactory testing be implemented as an early screening measure ( [11] , [12] , [13] , [14] , [15] ).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have demonstrated that cognitive impairment in older persons is related to general characteristics such as age, sex, and education [ 2 ], lifestyle factors such as drinking and smoking [ 3 ], and disease factors such as diabetes [ 4 ] and depression [ 5 ]. In recent years, many researchers have become increasingly interested in studies on the olfactory impairment observed in the early stages of neurodegenerative diseases, such as Alzheimer’s disease (AD), and Parkinson’s disease (PD), and cognitive impairment [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%